Tamoxifen treatment and its outcome in breast cancer patients at a hospital-based cancer registry in Kerala - Thomas, Reema A.; Nisha, Catherin (International Journal of Research in Medical Sciences, 2020)
Background: Endocrine therapy for breast cancer is directed at reducing oestrogen synthesis or alternatively blocking oestrogen receptors (ER) in tumour-sensitive tumors. Despite side effects, the use of systemic adjuvant therapy after local management of breast cancer substantially improves survival and reduces the risk of relapse. The study objective was to assess the recurrence of breast cancer and the complications seen in breast cancer patients on tamoxifen therapy at a hospital-based cancer registry, Thrissur, Kerala. Methods: After obtaining institutional ethical clearance, included 75 patients of histologically diagnosed breast carcinoma currently on tamoxifen, diagnosed in the year of 2016. Data was obtained from the patient files and by personal intimation. Results: Of the 75 patients on tamoxifen, four (5.33%) patients had history of recurrence. 22.6% of patients on tamoxifen were noted to have increased endometrial thickness. Other side effects noted were weight gain, TIA, bone pain and vaginal discharge. Conclusions: It was found that the recurrence rate at three years for the study population was 5.33%. More studies from developing countries, with larger sample size and clinical trials will give us more accurate information regarding the efficacy of the drug.